How local leaders shape development policies - Moore-Miggins, Deborah (CSIS Americas Program WashingtonUS, 1997)
Seeks and assesses the nature and extent of the role of local leaders in the formulation and implementation of development policies and addresses the experience of the Commonwealth Caribbean and Trinidad and Tobago.